Multi-User Channels With Large-Scale Antenna Arrays in a Subway Environment: Characterization and Modeling - Bei Zhang; Zhangdui Zhong; Ruisi He; Bo Ai; Ghassan Dahman; Mi Yang; Jianzhi Li (IEEE Access)
This paper presents results from an extensive measurement campaign of multi-user channels with large-scale antenna arrays (MULAs) in a subway station environment. Based on the measurements, two spatial separation metrics are characterized. The variance of user separability and temporal behavior are investigated. Furthermore, a MULA channel model with transmit correlation is proposed, which ensures that the MULA channels can be generated with a given degree of compatibility. The proposed MULA model is validated by comparing the distributions of the sum rate capacity and the condition number to measurements.